Humoral response against small heat shock proteins in Parkinson's disease. - Ewa Papuć; Ewa Kurys-Denis; Witold Krupski; Konrad Rejdak (PLoS ONE)
Introduction In the light of evidence for the increased heat shock proteins (HSP) expression in neurodegenerative disorders, the presence of the adaptive humoral response of the immune system can be expected. The aim of the study was to check whether Parkinson's disease (PD) has the ability to elicit immune response against small heat shock proteins. Methods IgG and IgM autoantibodies against alpha B-crystallin were assessed in 26 PD patients 26 healthy subjects. For the assessment of anti-HSP IgG autoantibodies serum samples from 31 parkinsonian patients and 31 healthy control subjects were collected. Serum samples from PD patients and healthy control subjects were collected twice, at baseline and after mean of 13 months follow up. Results Both IgM and IgG autoantibodies against alpha ß-crystallin in PD patients were significantly higher compared to healthy controls (p<0.05). We also found statistically significant increase in antibodies titers against alpha ß-crystallin over the time of 13 months, both for IgG (p = 0.021) and for IgM (p<0.0001). Additionally, PD patients presented higher levels of anti-HSP IgG autoantibodies than healthy controls (p = 0.02). Conclusions Increase of IgG and IgM autoantibodies against alpha B-crystallin in PD patients over time may suggest their involvement in the disease pathogenesis and progression. Further studies are required to confirm the role of this antibody as a biomarker of the disease progression.